If $A=\begin{bmatrix}1&0&0\\0&1&1\\0&-2&4\end{bmatrix},6A^{-1}=A^2+ cA + dI$, then $(c, d) =$ |
(-6, 11) (-11, 6) (11, 6) (6, 11) |
(-6, 11) |
Every square matrix A satisfies its characteristic equation i.e. $|A - λI| = 0$. Here, $|A - λI| = 0$ $⇒\begin{vmatrix}1&0&0\\0&1- λ&1\\0&-2&4- λ\end{vmatrix}=0$ $⇒(1-λ) \{(1-λ) (4-λ)+2\}=0$ $⇒λ^3-6λ^2+11λ-6=0$ $⇒A^3-6A^2+11A - 6I = 0$ $⇒6I = A^3-6A^2+11A$ $⇒6A^{-1} = A^2 -6A + 11I$ [Multiplying both sides by $A^{-1}$] $∴6A^{-1} = A^2 + cA + dI⇒c=-6$ and $d=11$ |